In-use energy and carbon performance of a true zero carbon housing development in England. (26th November 2021) - Oreskovic, Luka; Gupta, Rajat; Strong, David
Abstract : This paper systematically examines the in-use energy and carbon performance of a large case study housing development in England, designed to be net true zero carbon. Remote monitoring during a one-year period was used to gather high-frequency data on dwelling heat use, grid electricity use, solar PV electricity generation and export and community heating system performance. Based on data from 74 dwellings, mean energy use of 76 kWh/m 2 /year and electricity use of 27.4 kWh/m 2 /year per dwelling placed the case study among the lowest energy housing developments in the UK. Nonetheless, heat usage and designed fabric efficiency fell short compared to other true zero carbon housing. The mean self-consumption rate of generated energy of 23% calls for the provision of home batteries. Heat usage variance was more prominent compared to findings in other studies. Based on the 2018/19 carbon factors, dwellings emitted 20.2 kgCO2e/m 2 /year on average, missing the zero carbon target. As found in other studies, this was attributed to the underperforming community heating system. This study comes timely in the context of the widespread calls for net zero carbon dwellings. The findings confirm the argument that the anticipated mainstreaming of zero carbon dwellings demands shifting toward an outcome-focused design approach.